Synthesis of hydroxyapatite and fluorapatite nanoparticles with different amounts of fluoride using sol-gel method - Kia, Pooneh (2017)
Fluorapatite (FA) has been indicated as well alternative to pure hydroxyapatite (HA) in many reactions. Since the thermal decomposition and the poor corrosion resistance in an acid environment have restricted the applications of HA, as a solution, fluoride substitution in the structure of HA can improve the chemical stability and biocompatibility of HA nanoparticles. Therefore, FA nano particles can be used as a bioactive substance in the body, especially the teeth implants. Fluorhydroxyapatite (FHA) and FA nanoparticles were synthesized by adding the different amount of fluorine to the structure of HA using sol–gel method. Final products were characterized and optimized after different heat treatments of 700 °C to 1300 °C in order to improve its crystallinity. The aim of this study is to utilize sodium alginate (SA) as a bio-stabilizer in order to have the better precipitate which leads to having better crystallinity and smaller particle size. Calcium nitrate tetrahydrate, Ca(NO3)2•4H2O, diammonium phosphate (NH4)2HPO4, ammonium fluoride, NH4F, were used as precursors of Ca, P and F respectively with the ratio of 1:67 Ca/P, and pH kept between 10 - 11. The presence of HA and FA phase investigated by the results of x-ray diffraction (XRD) spektroscopy which confirmed the presence of all fluoride peaks more than 0.6 wt% in the structure of FA. Fourier-transform infra-red (FTIR) spectrum showed that fluoride was substituted by hydroxyl group in the samples which contained more than 0.6 wt% fluoride, while this could be describe by two evidences; disappearing the hydroxyl group at 3600 cm-1 and emerged of fluoride peak at 631 cm-1. Thermal gravimetric analysis (TGA) indicated that by increasing the amount of fluoride in the structure of apatite to more than 0.6 wt%, inevitably thermal stability increased. FA samples sintered at 700 ᴼC were observed to have average sizes of 50 nm and rod like shape, which were determined by TEM and SEM, respectively. Moreover, similar samples with SA indicated smaller particle size compared to those of without SA. From another aspect, SEM and TEM, samples sintered 1300 ᴼC indicated smaller size and finest nano rod like shape, 25 nm width and 8 nm in lengths for FA samples with SA. In conclusion, by using SA within the sol-gel method and increasing the amount of fluoride more than 0.6 wt% in the structure of HA, particle size significantly decreased and thermal stability remarkably improved.